Value assessment of PD-1/PD-L1 inhibitors in the treatment of oesophageal and gastrointestinal cancers - Ou, Shun-Long; Luo, Jing; Wei, Hua; Qin, Xiao-Li; Jiang, Qian (Frontiers in Pharmacology, 2023)
Background: Evidence of efficacy and safety of programmed cell death 1 (PD-1) and programmed death ligand-1 (PD-L1) checkpoint inhibitors in oesophageal cancer (EC), gastric cancer (GC) and colorectal cancer (CRC) was inconsistent, obscuring their clinical application and decision-making. The aim of this study was to comprehensively evaluate the value of PD-1/PD-L1 inhibitors in EC, GC and CRC to select valuable PD-1/PD-L1 inhibitors, and to assess the association between the value and cost of PD-1/PD-L1 inhibitors. Methods: A comprehensive search of trials of PD-1/PD-L1 inhibitors in EC, GC and CRC was performed in Chinese and English medical databases with a cut-off date of 1 July 2022. Two authors independently applied the ASCO-VF and ESMO-MCBS to assess the value of PD-1/PD-L1 inhibitors. A receiver operating characteristic (ROC) curve was generated to establish the predictive value of the ASCO-VF score to meet the threshold of the ESMO-MCBS grade. Spearman’s correlation was used to calculate the relationship between the cost and value of drugs. Results: Twenty-three randomized controlled trials were identified: ten (43.48%) in EC, five (21.74%) in CRC, and eight (34.78%) in GC or gastroesophageal junction cancer (GEJC). For advanced diseases, ASCO-VF scores ranged from −12.5 to 69, with a mean score of 26.5 (95% CI 18.4–34.6). Six (42.9%) therapeutic regimens met the ESMO-MCBS benefit threshold grade. The area under the ROC curve was 1.0 (p = 0.002). ASCO-VF scores and incremental monthly cost were negatively correlated (Spearman’s ρ = −0.465, p = 0.034). ESMO-MCBS grades and incremental monthly cost were negatively correlated (Spearman’s ρ = −0.211, p = 0.489). Conclusion: PD-1/PD-L1 inhibitors did not meet valuable threshold in GC/GEJC. Pembrolizumab met valuable threshold in advanced microsatellite instability–high CRC. The value of camrelizumab and toripalimab may be more worth paying in EC.